Pengaruh Locus of Control, Integritas Auditor, Dan Gaya Kepemimpinan Terhadap Kinerja Auditor Studi Kasus Pada Kantor Akuntan Publik di Kota Bandung - sabirin Sabirin (AKUNTANSI DEWANTARA, 2019)
The purpose of this study is to explain the Effect of Locus of Control, Auditor Integrity, and Leadership Style on Study Case Performance Auditors on Public Accountant Office in Bandung.The population in this study were the Auditors who had been Senior Auditors, Supervisors, and Managers who were still working in the Public Accountant Office registered at Indonesian Institute of Certified Public Accountants. The sample of this study is the Auditor who has been and is still working in Public Accountant Office who has been and is still serving as a Senior Auditor, Supervisor, and Manager at Public Accountant Office in the City of Bandung. The number of Public Accountant Office in Bandung City are 30 Public Accountant Office. To test the proposed hypothesis using Path Analysis model with multiple regression type method.The results of the study show that Locus of Control, Auditor Integrity, and Leadership Style have a significant positive effect on Auditor Performance. Case studies on Public Accountants in Bandung. Simultaneously Locus of Control, Auditor Performance, and Leadership Style have a significant positive effect on Auditor Performance Case studies in Public Accountants in Bandung.Keyword :Â Â  Locus of Control, Auditor Integrity, Leadership Style, Auditor Performance.